Peran Strategi Komunikasi Perpajakan dalam Meningkatkan Kepatuhan Pelaporan Surat Pemberitahuan Tahunan di Pelayanan Pajak Pangkalan Brandan - Tiara Ramadani; Muhammad Shareza Hafiz; Edy Suprayetno (Jurnal Riset AKuntansi dan Bisnis, 2026)
Taxpayer compliance in filing Annual Tax Returns (SPT) is a key indicator in the tax system. However, the level of SPT filing compliance in Indonesia still faces various challenges, particularly regarding understanding and communication. This study aims to analyze the role of tax communication strategies in improving compliance with Annual Tax Return filing at the Pangkalan Brandan Tax Office. The research method used is a qualitative approach with a literature review of various scientific sources from 2021–2025. The results show that effective communication strategies through outreach, digital education, and responsive service can increase taxpayer awareness and compliance.